A New Scoring System for Predicting In-hospital Death in Patients Having Liver Cirrhosis With Esophageal Varices - Xu, Fengshuo; Zhang, Luming; Wang, Zichen; Han, Didi; Li, Chengzhuo; Zheng, Shuai; Yin, Haiyan; Lyu, Jun (Frontiers in Medicine, 2021)
Introduction Liver cirrhosis is caused by the development of various acute and chronic liver diseases. Esophageal varices is a common and serious complication of liver cirrhosis during decompensation. Despite the development of various treatments, the prognosis for liver cirrhosis with esophageal varices (LCEV) remains poor. We aimed to establish and validate a nomogram for predicting in-hospital death in LCEV patients. Methods Data on LCEV patients were extracted from the Medical Information Mart for Intensive Care III and IV(MIMIC-III and MIMIC-IV) database. The patients from MIMIC-III were randomly divided into training and validation cohorts. Training cohort was used for establishing the model, validation and MIMIC-IV cohorts were used for validation. The independent prognostic factors for LCEV patients were determined using the least absolute shrinkage and selection operator (LASSO) method and forward stepwise logistic regression. We then constructed a nomogram to predict the in-hospital death of LCEV patients. Multiple indicators were used to validate the nomogram, including the area under the receiver operating characteristic curve (AUC), calibration curve, Hosmer-Lemeshow test, integrated discrimination improvement (IDI), net reclassification index (NRI), and decision curve analysis (DCA). Results Nine independent prognostic factors were identified byusing LASSO and stepwise regressions: age, Elixhauser score, anion gap, sodium, albumin, bilirubin, international normalized ratio, vasopressor use and bleeding. The nomogram was then constructed and validated. The AUC value of the nomogram was 0.867 (95% CI=0.832-0.904) in the training cohort, 0.846 (95% CI=0.790-0.896) in the validation cohort and 0.840 (95% CI=0.807-0.872) in the MIMIC-IV cohort. High AUC values indicated the good discriminative ability of the nomogram, while the calibration curves and the Hosmer-Lemeshow test results demonstrated that the nomogram was well calibrated. Improvements in NRI and IDI values suggested that our nomogram was superior to MELD-Na, CAGIB and OASIS scoring system. DCA curves indicated that the nomogram had good value in clinical applications. Conclusion We have established the first prognostic nomogram for predicting the in-hospital death of LCEV patients. The nomogram is easy to use, performs well, and can be used to guide clinical practice, but further external prospective validation is still required.